Disaster preparedness of registered nurses in a central hospital in Johannesburg - Messe, Lorato Baikanne (My University, 2017)
Background: Approximately 250 million people per year are affected by disasters (manmade or natural). In South Africa, the types of disasters that occur commonly are road accidents, manmade fires, explosions, storms, river floods and wild fires. The challenges faced in dealing with the complexity of disasters requires each nurse to have a knowledge base and minimum set of skills to enable them to plan for and respond to a disaster in a timely and appropriate manner. Purpose: To ascertain whether registered nurses, practicing in medical and surgical wards in a central hospital in Johannesburg are prepared for disasters. Design: A quantitative, descriptive, exploratory survey study design was used in this study. Method: The study was conducted in a central hospital in Johannesburg. A survey questionnaire, developed by Fung et al. (2008) and modified for the South African setting, was used for this study. The population for this study was 192 registered nurses, working in the medical and surgical wards of a central hospital in Johannesburg. A total sample of 192 participants was used. The data was analysed using descriptive statistics, ordinal logistic regression and summative content analysis. Statistical assistance was sought from a statistician. Results: Four major findings emerged from the data. The data revealed the majority of the nurses(52.45%: n=75)had not previously participated in disaster activities and had limited disaster training and education. Previous participation in disaster activity had influenced nurse’s disaster preparedness, however nurses perceived themselves generally prepared. Conclusion statement: even though nurses have indicated the need and interest in attending educational courses on disaster, the majority have not attended them. Disaster drills have also been found to be an important exercise to assist the nurses in disaster preparedness. Therefore hospitals are urged to be consistent with their disaster drills and regularly update their disaster management protocols. Clinical significance: An understanding of how prepared registered nurses perceive themselves to be, to respond to a disaster, would help assist in identifying the weaknesses and strengths in disaster preparedness in medical and surgical wards.
A research report submitted to the Faculty of Health Sciences,University of the Witwatersrand,Johannesburg in partial fulfillment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2017
Keywords: Disaster; Nurses